The theory-practice interplay in creating a graphic memoir about the trauma of forced migration. Issue 5 (3rd September 2021) - Appleton, Catherine
ABSTRACT: In my graphic memoir The Wounds of Separation I combined personal memory and historical fact incorporating conceptual insights to tell a story about the way traumas are remembered. The story describes the forced migration of a child and how,  in order to survive the devastation of WWII a young girl is separated from her parents and home causing lasting impacts on her life. The narrative content was enriched by a research process that involved understandings gained from trauma theories. In this paper I explore how these theoretical understandings shaped the creation of my graphic memoir and how representational theories helped direct the narrative choices to communicate the experience of trauma. I show how the conceptual underpinnings have been realised in my multimodal narrative identifying the text/image options that make the graphic memoir an appropriate representational choice. In my analysis of pages I describe the intended meanings I aim to communicate and explain the creative expression of those ideas.